2022
DOI: 10.1111/jth.15713
|View full text |Cite
|
Sign up to set email alerts
|

Molecular pathogenesis and heterogeneity in type 3 VWD families in U.S. Zimmerman program

Abstract: Background Type 3 von Willebrand Disease (VWD) is a rare and severe form of VWD characterized by the absence of von Willebrand factor (VWF). Objectives As part of the Zimmerman Program, we sought to explore the molecular pathogenesis, correlate bleeding phenotype and severity, and determine the inheritance pattern found in type 3 VWD families. Patients/Methods 62 index cases with a pre‐existing diagnosis of type 3 VWD were analyzed. Central testing included FVIII, VWF:Ag, VWF:RCo, and VWFpp. Bleeding symptoms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 43 publications
(107 reference statements)
1
3
0
Order By: Relevance
“…We depicted a full picture of the VWF domain distribution in different VWD types using all the so-far SNVs or short insertions/ deletions reported pathogenic VWF variants (n = 927). Our data showed that missense variants are responsible for the majority of reported and gnomAD variants, in agreement with established knowledge that the majority of type 1, almost all type 2 and some type 3 VWD are due to missense mutations [12][13][14][15] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We depicted a full picture of the VWF domain distribution in different VWD types using all the so-far SNVs or short insertions/ deletions reported pathogenic VWF variants (n = 927). Our data showed that missense variants are responsible for the majority of reported and gnomAD variants, in agreement with established knowledge that the majority of type 1, almost all type 2 and some type 3 VWD are due to missense mutations [12][13][14][15] .…”
Section: Discussionsupporting
confidence: 92%
“…Qualitative defects result in four different VWD types 2 (2A, 2B, 2M, and 2N) 11 . The genetic variants responsible for type 1 (mostly dominant) and 3 VWD (recessive) are spread across the 52 exons of VWF 12 14 , whereas type 2 VWD variants are confined to VWF functional domains 12 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Type 3 VWD is typically caused by recessive biallelic (homozygous or compound heterozygous) null VWF gene mutations across functional VWF domains, but with a higher incidence in the VWF pro-peptide region. 32 Type 2 von Willebrand Disease VWF functional defects cause type 2 VWD, but these may also be associated with quantitative deficiencies. Based on the VWF functional defect and multimer patterns, type 2 VWD can be classified into 2A, 2B, 2M, or 2N.…”
Section: Type 1 Von Willebrand Diseasementioning
confidence: 99%
“…Qualitative defects result in four different type 2 VWD (2A, 2B, 2M and 2N) [11]. The genetic variants responsible for type 1 (mostly dominant) and 3 VWD (recessive) are spread across the 52 exons of VWF [12][13][14], whereas type 2 VWD variants are con ned to VWF functional domains [12,15].…”
Section: Introductionmentioning
confidence: 99%